Charge. transport, conductivity and Seebeck coefficient in pristine and TCNQ loaded preferentially grown metal-organic framework films. (5th October 2022) - Chen, Xin; Zhang, Kai; Hassan, Zeinab Mohamed; Redel, Engelbert; Baumgart, Helmut
Abstract: This investigation on metal-organic framework (MOF) HUKUST-1 films focuses on comparing the undoped pristine state and with the case of doping by TCNQ infiltration of the MOF pore structure. We have determined the temperature dependent charge transport and p -type conductivity for HKUST-1 films. Furthermore, the electrical conductivity and the current–voltage characteristics have been characterized in detail. Because the most common forms of MOFs, bulk MOF powders, do not lend themselves easily to electrical characterization investigations, here in this study the electrical measurements were performed on dense, compact surface-anchored metal-organic framework (SURMOF) films. These monolithic, well-defined, and (001) preferentially oriented MOF thin films are grown using quasi-liquid phase epitaxy (LPE) on specially functionalized silicon or borosilicate glass substrates. In addition to the pristine SURMOF films also the effect of loading these porous thin films with TCNQ has been investigated. Positive charge carrier conduction and a strong anisotropy in electrical conduction was observed for highly oriented SURMOF films and corroborated with Seebeck coefficient measurements. Van der Pauw four-point Hall sample measurements provide important insight into the electrical behavior of such porous and hybrid organic–inorganic crystalline materials, which renders them attractive for potential use in microelectronic and optoelectronic devices and thermoelectric applications.